Still subjects? Why? – Thinking about these issues in everyday life (Práxis Educativa, 2024)
Starting from the idea of essay and the educative networks studied, as well as the necessary movements for research with the everyday life, we sought, in this text, to indicate how the Research Group Everyday life curricula, educative networks, images and sounds works, in the researches it carries out, with the idea of ‘cineconversas’ [movietalks]. In this process, we gather the actions of ‘seelistenfeelthink’ films and ‘readfeelthink’ texts of interest with groups of practicing and undergraduate teachers in the Brazilian cities of Manaus, in Amazonas; Salvador, in Bahia; Vitória-Serra, in Espírito Santo; and Nova Friburgo-São Gonçalo-Rio de Janeiro, in Rio de Janeiro. Working with acute social issues that are both ‘insideoutside’ schools, we give ‘spacetimes’ to teacher narratives, seeking to understand possibilities to go beyond the structure in subjects of curricula, proposed over two centuries ago.Keywords: Educative networks. Movietalks. Beyond subjects.